A Model to Strengthen Early Childhood Religious and Moral Education through Prophet Muhammad’s Example in Islamic-Based Early Childhood Institutions - Sholekah, Mar’atus; Khunaifi, Agus (FKIP - Universitas Riau, 2026)
This study aims to analyze the learning model of religious and moral education in early childhood through the example of the Prophet Muhammad SAW. The research method used is qualitative with a case study approach at TPA/KB/RA Al-Muna, an Islamic-based early childhood education institution. The research subjects included children aged 4–6 years, with data obtained through observation, interviews, and documentation, then analyzed descriptively-qualitatively. The results of the study indicate that the strengthening of religious and moral education is carried out through internalization of the exemplary values of the Prophet Muhammad SAW in various learning activities, including storytelling, the use of visual media, and role-playing that depicts the morals of the Prophet. These findings confirm that the model of strengthening religious and moral education through the example of the Prophet at TPA/KB/RA Al-Muna applies an integrative exemplary method. Exemplary behavior is combined with other aspects, namely patience and perseverance, and also diverse learning resources. Therefore, this strategy is recommended to be implemented systematically in the Islamic-based early childhood education curriculum.